2017
DOI: 10.1111/gcbb.12423
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of bioenergy wood production from poplar short‐rotation coppice grown at a marginal agricultural site in Germany

Abstract: For avoiding competition with food production, marginal land is economically and environmentally highly attractive for biomass production with short-rotation coppices (SRCs) of fast-growing tree species such as poplars. Herein, we evaluated the environmental impacts of technological, agronomic, and environmental aspects of bioenergy production from hybrid poplar SRC cultivation on marginal land in southern Germany. For this purpose, different management regimes were considered within a 21-year lifetime (combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 89 publications
(115 reference statements)
1
23
0
Order By: Relevance
“…Based on these results, fertilisation of young poplar plants is not necessary and can be deferred during the first years. Another marginal agricultural land in southern Germany did not confirm these results [13], which may be explained by a higher mean annual precipitation rate of 790 mm year −1 supporting a less restricted nutrient availability and a better growth. But the authors reported that the benefits of fertiliser-induced higher biomass yields did not counterbalance the negative environmental impacts as for example the leaching of NO 3 − , which had been identified as the main pathway for N loss from the sandy soil of our study site, primarily in the winter when high seepage rates emerged.…”
Section: Perspectives For Adjusted Fertilisation Of Srcmentioning
confidence: 78%
See 1 more Smart Citation
“…Based on these results, fertilisation of young poplar plants is not necessary and can be deferred during the first years. Another marginal agricultural land in southern Germany did not confirm these results [13], which may be explained by a higher mean annual precipitation rate of 790 mm year −1 supporting a less restricted nutrient availability and a better growth. But the authors reported that the benefits of fertiliser-induced higher biomass yields did not counterbalance the negative environmental impacts as for example the leaching of NO 3 − , which had been identified as the main pathway for N loss from the sandy soil of our study site, primarily in the winter when high seepage rates emerged.…”
Section: Perspectives For Adjusted Fertilisation Of Srcmentioning
confidence: 78%
“…Fertilisation can increase the yield of woody biomass and thus its fossil fuel substitution potential [9,10]. However, it must be taken into account that due to intensive soil management, environmental impacts such as amplified NO 3 − leaching and greater emission of GHG from the soil may occur during the production of trees [11][12][13]. Alongside tillage and harvesting, N fertilisation has often been identified as the operation responsible for NO 3 − leaching and the emission of N 2 O [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the use of several indicators and the combination of different methods to calculate indicator values lead to a strong analytical power for embracing financial, technological, environmental and other aspects of a production system, e.g., [37]. In particular, the feature of Umberto to include 'own' indicators and data, as well as data from the database Ecoinvent turned out to be efficient and productive.…”
Section: Discussionmentioning
confidence: 99%
“…), we apply the following extended equation: UE BM and UE fossil denote upstream emissions per energy unit of biomass and fossil fuel, respectively. Combustion emission factors are taken from IPCC Guidelines (IPCC, 2006a), and upstream emissions are based on literature data (Bradbury, Obeiter, Draucker, Wang, & Stevens, 2013;Brandt, 2011;EC, 2015;Giuntoli, Agostini, Edwards, & Marelli, 2015;Schweier et al, 2017;Scull et al, 2017). Depending on transport distances and modes, characteristics of fossil fuel deposits and other influencing factors, upstream emissions vary widely.…”
Section: Calculation Of Carbon Dfsmentioning
confidence: 99%